Commuter housing arrangement in beji sub-district, Depok City, West Java / Nabilah Rizki Novani, Nurrokhmah Rizqihandari and Maria Hedwig Dewi Susilowati - Rizki Novani, Nabilah; Rizqihandari, Nurrokhmah; Hedwig Dewi Susilowati, Maria (Universiti Teknologi MARA, Perak, 2022)
Greater Jakarta has a high sprawling urban area for the whole city. Beji Sub-district in Depok is the home of Jakarta's commuters. With the high density of the residential area with various housing types, commuters who stay in this area have many living options. Respondents in this study are commuters who work in the DKI Jakarta area and stay in Beji Subdistrict, Depok City. The research questions of this study focus on how the relationship between accessibility factors and the variation of housing chosen by commuters in Beji District, Depok City, and how the factors of a residential area, number of dwelling members, and social facilities influence the decision of commuters to live in housing in Beji District, Depok City. The objective of this study is to determine the factor that had influenced commuters' housing choices. With chi-square analysis, the accessibility level had a significant relationship with the type of housing arrangement; most commuters live in the landed house in residential areas with easier access. According to the multinomial logistic regression model, the most influential factor was the number of dwelling members. Commuters living in a rented house with 1 – 2 members are twice as likely to live in a boarding house. Commuters living in apartments 3,8 times chose near education facilities than commuters living in a boarding house. Lastly, commuters living in the landed house were not influenced by any variable in this study.